Refusal Strategies Employed by Senior High School English Teachers in Adonara Timur: A Pragmatic Study - Muda, Agnes; Toni, Elvis Albertus Bin (Universitas Pahlawan Tuanku Tambusai, 2026)
Refusal is a complex pragmatic act that often entails face-threatening consequences, requiring speakers to balance clarity, politeness, and interpersonal harmony. This study examines the refusal strategies employed by senior high school English teachers in Adonara Timur when responding to requests outside the classroom context. Using a qualitative research design and content analysis, data were collected from 13 teachers through a Discourse Completion Test (DCT) consisting of ten situational scenarios. The responses were analyzed using Beebe, Takahashi, and Uliss-Weltz’s (1990) taxonomy of refusal strategies. Findings show that indirect refusal strategies—such as providing explanations, expressing regret, offering alternatives, and citing external circumstances—were the most frequently used. Teachers also consistently employed adjuncts, including expressions of gratitude, appreciation, and apologies, to mitigate the force of their refusals and maintain positive interpersonal relationships. Direct refusal strategies appeared less frequently and were mostly used in situations involving institutional rules or established agreements, particularly in interactions with students. Overall, the study highlights the teachers’ strong orientation toward politeness, relational harmony, and context-sensitive communication. These findings contribute to understanding the pragmatic competence of English teachers in Indonesian educational settings and offer insights for integrating pragmatic awareness into language teaching materials and professional development programs.